Android Smartphone Damage Diagnosis Expert System by Web-Based Forward Chain Method - Andri Nofiar Am; Fina Nasari (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Android smartphones are commonly used smartphones. Smartphone damage often plagues smartphone users nowadays, and the user should bring the smartphone to his smartphone service provider to find out what kind of damage has happened to the device. The repair time consumed while the user's smartphone is at a service point can also consume the user's time, not to mention the cost of the repair and the distance traveled to the smartphone's service point can be significant. That's why we created an expert system for diagnosing damage to Android smartphones. When creating the system, the forward chain method was used to determine solutions to overcome smartphone damage and damage. The results of an expert system that uses a website-based forward-chain method to diagnose Android smartphone damage produces an expert confidence value that is processed before being used by the system. With this expert system, the researchers hope to help Android smartphone users deal with damage caused to their smartphones.